In vivo evaluation of the accuracy of an electronic apex locator in root canal length determination in primary teeth - Shahrabi M; Seraj B; Heidari A (Tehran University of Medical Sciences, 2006)
Background and Aim: Radiography is the most commonly used technique in root canal length determination, but its application in pedodontics is difficult due to many problems such as radiation hazards, superimposition of permanent teeth buds and uncooperative children. The aim of this study was to investigate the accuracy of an electronic apex locator (Dentaport ZX) in measuring the root canal length of primary teeth in vivo. Materials and Methods: In this test evaluation study, pulp tissues of 52 primary teeth planned to extraction were removed and the canal length were measured by Dentaport ZX. After extraction, real lengths of canals were measured by using# 15 K-Type file with 0. 1 mm accuracy and both measurements were compared. Data were analyzed by Smirnov Kolmogorov, chi-square, ANOVA and intraclass correlation and p<0.05 was considered as the limit of significance. Results: The difference between the canal lengths measured by eye and Dentaport ZX was-0.17±0.384 mm. Maximum deviation of the real length of canals was between-0.2 to+0.2 mm from apical foramen. Accuracy of Dentaport ZX in the range of-0.2 to+0.2 from apical foramen was 66.96% and in the range of-0.5 to+0.5 from apical foramen was 92.17%. Conclusion: Based on the results of this study, the use of Dentaport ZX in endodontic treatment for primary teeth could be advisable.